Cowboy Creativity: An Economic Future for Rural Flint Hills Communities - Christy Davis (Symphony in the Flint Hills, 2016)
In spring 1875 a cowboy walked into Charles Hyer’s boot shop in Olathe, Kansas, with a special request. He wanted boots that were comfortable for riding and walking with toes that would easily slip into stirrups.
Keywords: cowboy; cowboy boots; farmers; ranchers; Chase County; Flint Hills; landscape; postwar; businesses; culture; rural communities; Flint Hill Sojourning; Chiyoko Myose; Primary Grazer; Matt Regier; GRASSES – SILVER RIBBONS; Chris Wolf Edmonds; LANDSCAPE IN A LANDSCAPE; Derek Dobbins